GERAKAN SALAFIYYAH DI PONDOK PESANTREN DHIYAâUSSALAF MUARA ENIM SUMATERA SELATAN - Muhammadin, Muhammadin (Intizar, 2015)
AbstractThis paper is derived from the results of research that examines the understanding and factors underlying the emergence of Salafiyyah movement in Dhiyaussalaf boarding school. Methodologically, this is a field researchÂ that uses the paradigm of qualitative or naturalisticÂ inquiry.Â It has been on the consideration of the analysis of the research problem that requires some information based on the principles of qualitative research. The primary method of collecting the data is through direct and in-depth interviews with the students and teachers at Dhiyaussalaf boarding school. In addition, observation that does not interfere with the natural setting or the authenticity was conducted. These research data was analyzed on a case-qualitative, which began collecting the data in the field. To get the data which were not only descriptive but also able to touch the transcendent dimension, the creative divergent thinking was then sought after. This paper concludes that the understanding pattern of Salafiyyah movement in Dhiyaussalaf boarding school has the act based on Sunnah. The act exemplified by the tabiin has a missionary with tashfiyah principle in the sense of purification of Islam including bidâah and hizbiyyah or harakiyyah. In addition, the school has principle in the sense of propaganda by fostering people to be a man who is able to live independently and to be perfectly servitude to God.Â Keywords:Â salafiyyah movement, dhiyaussalaf boarding school